Assessing Entrepreneurial Awareness, Interest, and Skill Development Approaches Among Electrical Installation and Maintenance Works Students in Technical Colleges of Adamawa State for Self-Employment - Zambwa, Joseph; Tumba, Ishaya; Falama, Rabiu (Darul Yasin Al Sys, 2024)
This study assessed entrepreneurial awareness, interest, and skill development approaches among EIMW students in GSTCs in Adamawa State for self-employment. The study employed a descriptive survey research design, targeting 217 respondents, including administrators, teachers, and students from three GSTCs in Adamawa State. Data was collected using a structured questionnaire and analyzed using mean statistics and ANOVA at a 0.05 level of significance. The findings revealed that EIMW students possess a moderate level of awareness of entrepreneurship, with many students lacking sufficient exposure to entrepreneurship concepts in their curriculum. The study also found a moderate level of interest in entrepreneurship among the students, with limited practical exposure contributing to a lack of enthusiasm for self-employment. Additionally, key strategies for entrepreneurial skill acquisition were identified, including providing rewards for innovation, aligning entrepreneurial content with market needs, and fostering creativity through institutional support. The study concludes that while students show potential for entrepreneurial success, more emphasis needs to be placed on entrepreneurial education and practical exposure. Recommendations include Government should organize entrepreneurship awareness campaign in all Government Technical Colleges in order to create more awareness among students in the Technical College.